Navigating corporate cultures from within : making sense of corporate values seen from an employee perspective - Jakobsen, Michael; Worm, Verner (Emerald Publishing Limited, 2022)
Navigating Corporate Cultures From Within offers a unique perspective on the management of headquarter-subsidiary-host market relationships with important insights on how to align corporate values with a localized mindset among culturally diverse employees and across a global enterprise. The shared norms and values that constitute a specific cultural setting supposedly create a common background for using a collective 'we' when referring to every individual employee in the organization. Yet, company values are engineered over time, are molded, and redesigned to match ongoing changes in both the external and internal environment, and their aim is to make the organization adapt faster to changing market conditions, globally as well as in local host markets. This study takes a closer look at the dynamic process of cultural renewal in a complex multinational organization with a particular focus on the role assumed by the individual employees. This is an entirely new way of looking at the effects of important corporate values where a common approach previously has been to look at organizational culture from a confined top management perspective. The findings in this book will be essential to the management of multinational enterprises.
Keywords: Corporate culture.; Business & Economics, Workplace Culture.; Organizational theory & behaviour.; elektronické knihy; electronic books